2016
DOI: 10.1039/c5ta07818k
|View full text |Cite
|
Sign up to set email alerts
|

Partially unzipped carbon nanotubes for high-rate and stable lithium–sulfur batteries

Abstract: Partially unzipped MWCNTs provide increased surface area and accessible inner pores with oxygen groups leading to high performance sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…The electrode materials, moreover, have insulating properties and exhibit massive volumetric expansion during redox reactions, which impedes the commercialization of Li S batteries. 16,17 Metal-organic frameworks (MOFs) are structured materials assembled by the coordination of inorganic clusters or ions with organic ligands. Since the pioneering work of Yaghi et al, a wide variety of MOFs with different compositions and structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode materials, moreover, have insulating properties and exhibit massive volumetric expansion during redox reactions, which impedes the commercialization of Li S batteries. 16,17 Metal-organic frameworks (MOFs) are structured materials assembled by the coordination of inorganic clusters or ions with organic ligands. Since the pioneering work of Yaghi et al, a wide variety of MOFs with different compositions and structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…High conductivity, appropriate porosity and high mechanical strength are essential for nanostructured sulfur host materials [7]. Various carbon materials, for instance microporous carbon [8], mesoporous carbon [9], hierarchical porous materials [10], carbon nanotubes [11,12] and carbon fibers [13], have been used as host materials of sulfur in Li-S batteries. However, the weak interaction between polar lithium polysulfides and non-polar porous carbon materials could still results in severe shuttle effect, e.g., the irreversible loss of lithium polysulfides from electrodes and therefore significant decay of Li-S battery over long-term cycling [14].…”
Section: Introductionmentioning
confidence: 99%
“…Oriented material designs have been deemed as one of effective strategies to address the aforementioned challenges and promote the development of advanced lithium (Li) batteries for practical application. [9][10][11][12][13][14][15] Naturally biomass materials always exist in the form of biological macromolecules or carbohydrate compounds in plant or animal cells, which endow themselves with diverse microstructures, complex compositions, and abundant functional groups. These unique physicochemical properties offer an emerging opportunity to compatible with high-energy advanced lithium batteries.…”
mentioning
confidence: 99%